Assessment of trace metals contamination level, bioavailability and toxicity in sediments from Dakar coast and Saint Louis estuary in Senegal, West Africa. (November 2015) - Diop, Cheikh; Dewaelé, Dorothée; Cazier, Fabrice; Diouf, Amadou; Ouddane, Baghdad
Highlights: Trace metals were analysed in sediment from African coast and estuary. Geochemical normalisation performed to evaluate anthropogenic influences on the sediments. Strong pollution and potential toxicity which may constitute a risk to populations' health. Concentrations of trace metals were above threshold limit of the sediment quality guidelines. Abstract: Trace metals have the potential to associate with sediments that have been recognised as significant source of contamination for the benthic environment. The current study aims assessing the trace metals contamination level in sediments from Dakar coast and Saint Louis estuary, and to examine their bioavailability to predict potential toxicity of sediments. Surface sediment samples were collected between June 2012 and January 2013 in three sampling periods from eight stations. Trace metals were analysed using inductively coupled plasma-optical emission spectrometer. Geoaccumulation indexes (Igeo) showed strong pollution by Cd, Cr, Cu and Pb confirmed by enrichment factor (EF) suggesting that these metals derived from anthropogenic sources. Toxicity indexes exceeded one in several sites suggesting the potential effects on sediment-dwelling organisms, which may constitute a risk to populations' health. However, seasonal variability of metal bioavailability was noted, revealing the best period to monitor metal contamination. From an ecotoxicological point of view, concentrations of Cd, Cr, Cu and Pb were above the effects range low threshold limit of the sediment quality guidelines for adverse biological effects. In addition, with Pb concentrations above the effect range medium values in some sites, biological effects may occur.